'The New Experimentalists', Queen Elizabeth Hall, London, 14 January 2014. (16th June 2014) - Graham, Cameron
Abstract : Considering the reputation of the Southbank Centre as a major British authority on new music and art, their playing host to 'The New Experimentalists' in January seemed a long time coming. From an institution one year into its twentieth-century musical extravaganza, The Rest Is Noise Festival, an evening highlighting new and recent works by four leading experimental artists came as a welcome break from an exhaustive list of twentieth-century 'classics'.